The Big Data Technologies as an Important Factor of Electronic Data Processing and the Development of Computerized Analytical Platforms, Business Intelligence - Sylwia Gwoździewicz; Dariusz Prokopowicz (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
The development of transformation and sharing information via the Internet has been determined by numerous facilities for beneficiaries, clients and those using information services of the public sector institutions. Moreover, there is an opportunity for the entities sharing electronic information via the Internet to significantly reduce transactional costs of their performed financial operations and electronic data transfer. On the other hand, the information technology (IT) development functioning in the Internet is connected with the risk of losing and theft of information by unentitled entities. The process of sharing information via the Internet generates many threats connected with identity theft crime, taking over secret data by hackers and embezzlement of money in the electronic banking systems. In response to the threats, particular entities, including the institutions of the financial sector, develop security systems of remote information sharing and performing transactions via the Internet. Nowadays, there is a continuity of the technique improvement process providing certain level of the Internet security data transfer. The procedures of safe transforming, stocking and sharing information in the Internet electronic banking have been being improved. National legal regulations considering new occurring technology innovation and electronic transfer technologies in the Internet have been being completed as well. Dissemination of standards of performing financial operations in the cloud as well as those huge data collections allocated in the big data platforms are within the fasted developing IT areas that determine further phases of advance of the electronic Internet banking.